2007
DOI: 10.1152/jn.01001.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Perceptual Learning on Local Stereopsis and Neuronal Responses of V1 and V2 in Prism-Reared Monkeys

Abstract: Visual performance improves with practice (perceptual learning). In this study, we sought to determine whether or not adult monkeys reared with early abnormal visual experience improve their stereoacuity by extensive psychophysical training and testing, and if so, whether alterations of neuronal responses in the primary visual cortex (V1) and/or visual area 2 (V2) are involved in such improvement. Strabismus was optically simulated in five macaque monkeys using a prism-rearing procedure between 4 and 14 wk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 83 publications
2
16
0
Order By: Relevance
“…Here we document recovery of stereopsis through PL in human adults who are stereoblind or severely stereodeficient. Our results are consistent with the recent report of Nakatsuka et al (13) that adult monkeys with mild stereo deficiencies (i.e., that required a larger depth cue) improved their stereoacuity through PL. However, these investigators were unable to train monkeys with severe deficits (e.g., that had no response to depth cues).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Here we document recovery of stereopsis through PL in human adults who are stereoblind or severely stereodeficient. Our results are consistent with the recent report of Nakatsuka et al (13) that adult monkeys with mild stereo deficiencies (i.e., that required a larger depth cue) improved their stereoacuity through PL. However, these investigators were unable to train monkeys with severe deficits (e.g., that had no response to depth cues).…”
Section: Discussionsupporting
confidence: 93%
“…It seems that the strong suppression of the NDE by the DE has little effect on the stereo performance in the recovered stereopsis for our amblyopic/strabismic observers. This surprising result may be relevant to the neurophysiological data reported by Nakatsuka et al (13), which imply that the improvement of disparity sensitivity in prism-reared monkeys occurs primarily beyond cortical area V1.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…For example, Nakatsuka et al (2007) reported that adult monkeys reared with prisms had mild stereo deficiencies that improved through PL after 10,000– 20,000 trials.…”
Section: Can Stereopsis Be Recovered In Children and Adults With Amentioning
confidence: 99%
“…However, there are a limited number of experimental studies documenting recovery of stereopsis in adults who have long been deprived of normal binocular vision. Nakatsuka et al [6] reported that adult monkeys reared with prisms had mild stereo deficiencies that improved through perceptual learning (PL) after 10 000-20 000 trials. Astle et al [7] reported on two cases of humans with anisometropic amblyopia whose stereopsis improved following a learning-based course of training, which included refractive adaptation followed by monocular PL as well as stereoscopic PL.…”
Section: Introductionmentioning
confidence: 99%